2022
DOI: 10.3390/foods12010135
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Hemp Seed Oil Quality Pressed from Fresh and Stored Seeds of Henola Cultivar Using Differential Scanning Calorimetry

Abstract: Cold-pressed hemp (Cannabis Sativa L.) seed oil has become very popular amongst consumers and researchers, due to its manifold application in food and medicine industry. In this study, oils pressed from stored and fresh hemp seeds of the Henola cultivar were analyzed. Determination of the acid value (AV) and color of oil (a* parameter) revealed significant differences between the two groups of oils (fresh and stored seeds) in contrast to the peroxide value (PV), p-anisidine value (p-AV), and fatty acid composi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 32 publications
1
4
0
Order By: Relevance
“…Moreover, this variety achieved the best efficiency in terms of the pressing process both at low temperatures (>69%) and at high temperatures (>79%). Islam et al [32] previously indicated that the oil yield increases with an increase in the processing temperature, which was confirmed by the results obtained in this study. Moreover, pressing the Secuieni Jubileu variety, which has the largest seeds, showed the lowest efficiency when pressed at low temperatures.…”
Section: Resultssupporting
confidence: 92%
“…Moreover, this variety achieved the best efficiency in terms of the pressing process both at low temperatures (>69%) and at high temperatures (>79%). Islam et al [32] previously indicated that the oil yield increases with an increase in the processing temperature, which was confirmed by the results obtained in this study. Moreover, pressing the Secuieni Jubileu variety, which has the largest seeds, showed the lowest efficiency when pressed at low temperatures.…”
Section: Resultssupporting
confidence: 92%
“…The expressed colour contents of the baobab seed oil are based on the Hunter ( Lab ) and CIELAB ( L ∗ a ∗ b ∗ ) scales. The L / L ∗ shows that the baobab seed oil for both methods were lighter in colour; that is, both values exceeded 51 points on the scale of 51–100 as in Islam et al [ 48 ] and Dodoo et al [ 49 ]. The values of L / L ∗ for the mechanical and Soxhlet extractions were found to be 61.99/68.37 and 69.70/72.19, respectively.…”
Section: Resultsmentioning
confidence: 65%
“…Hemp seed oil (HSO) is known as a functional food [78]. It is rich in essential fatty acids, with a PUFAs content of over 80% [79]. The PUFAs most prominently presented in HSO are linoleic and α-linolenic acids, with a content of 50-70% and 15-25% of total oil, respectively [80].…”
Section: Hemp Seed Oil and Evening Primrose Oilmentioning
confidence: 99%